2018
DOI: 10.1097/ogx.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Risk Identification and Reduction of Cardiovascular Disease in Women Through Collaboration With Obstetricians and Gynecologists: A Presidential Advisory From the American Heart Association and the American College of Obstetricians and Gynecologists

Abstract: (Abstracted from Circulation 2018;137(24):e843–e852) Many traditional atherosclerotic cardiovascular disease (ASCVD) risk factors, such as hypertension, diabetes mellitus, hypercholesterolemia, and obesity, may affect women more than men and in many cases more severely. Cardiovascular mortality is greater in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 0 publications
0
40
0
1
Order By: Relevance
“…Counselling regarding heart disease risk as well as risk factor modification and treatment can only occur if medical providers are both aware of the association of non-traditional risk factors with CVD and obtain a history of these. The American Heart Association and College of Obstetricians and Gynecologists has called for increased screening for non-traditional CVD risk factors in women, along with appropriate follow-up to mitigate risk [8]. Current cardiovascular risk assessment algorithms included in the Australian Heart Foundation and Cardiac Society of Australia and New Zealand guidelines, such as the Global Registry of Acute Coronary Events (GRACE) score, do not include adverse pregnancy history in risk prediction models for future risk of CAD [9].…”
Section: Discussionmentioning
confidence: 99%
“…Counselling regarding heart disease risk as well as risk factor modification and treatment can only occur if medical providers are both aware of the association of non-traditional risk factors with CVD and obtain a history of these. The American Heart Association and College of Obstetricians and Gynecologists has called for increased screening for non-traditional CVD risk factors in women, along with appropriate follow-up to mitigate risk [8]. Current cardiovascular risk assessment algorithms included in the Australian Heart Foundation and Cardiac Society of Australia and New Zealand guidelines, such as the Global Registry of Acute Coronary Events (GRACE) score, do not include adverse pregnancy history in risk prediction models for future risk of CAD [9].…”
Section: Discussionmentioning
confidence: 99%
“…92 More comparative studies should be performed in order to define the most accurate risk index for pregnant women with heart disease. 91,95 The role of comprehensive cardio-obstetric clinics The concept of multidisciplinary cardio-obstetric clinics (Figure 10) has evolved and been applied in several countries, with extremely encouraging results [96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] and excellent survival rates of mothers even with complex diseases, and their offspring. 24 However, the need for cardio-obstetric clinics remains un-met, with most programs to be found in developed countries and with only a few centers continuing follow-up long term.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Even after resolution of symptoms, an elevated risk for future maternal cardiovascular, cerebrovascular, and vascular disease exists. [98][99][100][101][102][103][104][105][106][107][108][109][110] In addition, even though less investigated, several studies have already demonstrated that children antenatally exposed to pre-eclampsia are at an increased risk of long-term cardiovascular, respiratory neuropsychiatric, gastrointestinal, and endocrinological morbidity. [111][112][113][114][115]…”
Section: Conditionalmentioning
confidence: 99%
“…102 The American College of Obstetricians and Gynecologists (ACOG), with the AHA, has published a presidential advisory with the AHA providing specific recommendations for cardiovascular disease risk factors screening for women with prior pre-eclampsia that was preterm (<37 weeks) or recurrent. 103 In this group of women, ACOG recommends yearly screening of blood pressure, lipids, fasting blood sugar, and body mass index.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation